Comparison of Trading Volume and Share Price Changes Prior to and Following the Announcement of Dividend Tax Policy the Omnibus Job Creation Act - Sri Setia Ningsih; Lestari Adhi Widyowati (Quantitative Economics and Management Studies, 2023)
The study goal is to examine changes in trading activity and stock prices both before and after omnibus law on job creation Law dividend tax policy went into effect. The approach adopted in this study is an event study with matched samples from various tests. The consumer goods industry sector companies in the JII index listed on the IDX before and after announcement of the dividend tax policy are the research population. According to the research, there is a substantial difference between the periods before and after the introduction of the dividend tax policy on omnibus law in the variable stock trading volume, but not for variable share price. In order to provide investors with a guide when making investments in the nation, this study looks at and analyzes both long- and short-term changes in trading volume and stock prices before and after introduction of the dividend tax policy.